Cross-shelf movement of Chrysaora fulgida (Scyphozoa; Discomedusae) off Namibia inferred from stable isotopes (δ15N and δ13C). Issue 1 (2nd January 2021) - Skrypzeck, H; van der Lingen, CD; Gibbons, MJ
Abstract : Large and small specimens of two species of metagenic Scyphozoa (true jellyfishes) can be found in nearshore waters off central Namibia throughout the year. Whereas populations of Chrysaora africana are largely restricted to inshore waters, C. fulgida occurs across the shelf, with small individuals found inshore and large individuals primarily found offshore. We examined stable isotopes δ 15 N and δ 13 C of both species in Walvis Bay and found that large-sized C. fulgida have lower δ 15 N values than small individuals and C. africana throughout the year. These differences are interpreted to reflect cross-shelf changes in δ 15 N baseline levels, with greater nitrogen recycling (and hence lower δ 15 N values) occurring offshore. The occasional/seasonal nearshore appearance of large C. fulgida with low δ 15 N values therefore implies routine, onshore advection. The values of δ 13 C did not show cross-shelf differences, which suggests that jellyfish populations across the shelf are supported by phytoplankton-based food chains. This study emphasises the value of using stable isotopes to examine the mesoscale structuring of jellyfish populations.